Relationship between Innovation and Corporate Performance in Japanese SMEs by Two-stage Panel Data Analysis: Focusing on the Joint Effect of ICT and R&D - Taisuke Matsuzaki; Hidenori Shigeno; Sheikh Abu Taher; Masatsugu Tsuji (International Telecommunications Society (ITS), 2022)
The innovation theory tends to focus on innovation capabilities and estimate how these promote innovation. However, the final aim of innovation is not innovation itself but enhancing profits or sales. To complete the innovation theory, it is required to show whether innovation achieved contributes to improve in business performances. A further focus of this paper is on the role of ICT and R&D in the innovation process. ICT plays a vital role in absorbing information from outside the firm, while R&D is essential for assimilating obtained information with existing resources to create something novel. This paper focus on the joint effect of these two factors. The estimation is based on the twostage provit IV panel model and authors' own data of 2012 and 2017. The dependent variables are innovation in the first equation and sales in the second. The results obtained show that (i) Innovation enhances sales; (ii) R&D is significant for innovation; (iii) ICT is not significant for neither of equations; and (iv) the cross term of R&D and ICT is significant for innovation, implying ICT is an enabler of innovation. This is a novel result of the paper.
Keywords: 330; Open innovation; instrumental variable; mediation; cross term; enabler